Fault complexity degree in a coal mine and the implications for risk assessment of floor water inrush - Dandan Wang; Wanghua Sui; Zhiqiang Ji (Geomatics, Natural Hazards & Risk, 2024)
Faults significantly affect the stability of surrounding rock and stress distribution, which increases the possibility of water inrush disasters in a coal mine. Also, the precisely advanced prevention and control of floor limestone water become the foundation of ensuring mine safety and efficient production in coal mines. Fault development evaluation is one of the elements that control further transparent and fine studies. In this paper, the fault control index (FCI) is built based on the fractal dimension (Ds) and fault influence factor (E), which is determined according to the measured water inflow of water inrush points. The box meshing level is analyzed to calculate and compare the FCI. The results show that the box-meshing level affects the value of Ds and FCI and a meshing level of 6 seems to be the minimum standard of Ds for high accuracy. To verify the results, a comprehensive risk evaluation model of floor water inrush is established to illustrate the implications of fault complexity degree on safety mining. A stricter meshing grade when using the box-counting method in fault complexity degree is necessary for further studies in the precise prevention and control of mine hazards.